A fuzzy variable structure controller for STATCOM - Morris, S (2003)
Two new variable structure fuzzy control algorithms are presented in this paper for controlling the reactive component of the STATCOM current in a power system. The control signal is obtained from a combination of generator speed deviation and STATCOM bus voltage deviation fed to the variable structure fuzzy controller. The parameters of these fuzzy controllers can be varied widely by a suitable choice of membership functions and parameters in the rule base. Simulation results for typical single-machine and multimachine power systems subject to a wide range of operating condition changes confirm the efficiency of the new controllers. (C) 2002 Elsevier Science B.V. All rights reserved.